2020
DOI: 10.1080/08276331.2020.1786645
|View full text |Cite
|
Sign up to set email alerts
|

Model for stimulating entrepreneurial skills through entrepreneurship education in an African context

Abstract: The need to stimulate entrepreneurial skills in graduates as a strategy for tackling graduate unemployment has spurred the introduction of entrepreneurship education programs. The effectiveness of such entrepreneurship education programs from an African context is the focus of this paper. A modified model for evaluating the effectiveness of entrepreneurship education was derived from Fayolle, Gaily, and Lassa-Clerc; and was tested via structural equation modeling. Data were collected from randomly selected 750… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
1
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 46 publications
1
32
1
4
Order By: Relevance
“…That said, experiential pedagogy is clearly more helpful for both perception of change and the level of skills in comparison to traditional pedagogy. This provides a counter-evidence to the study of Olutuase, Brijlal, and Yan (2020) who found no effect of teaching method on generic entrepreneurial skills (creativity and innovation, flexibility and adaptability, etc.) outlined in Bacigalupo et al (2016).…”
Section: Confirmedcontrasting
confidence: 76%
See 2 more Smart Citations
“…That said, experiential pedagogy is clearly more helpful for both perception of change and the level of skills in comparison to traditional pedagogy. This provides a counter-evidence to the study of Olutuase, Brijlal, and Yan (2020) who found no effect of teaching method on generic entrepreneurial skills (creativity and innovation, flexibility and adaptability, etc.) outlined in Bacigalupo et al (2016).…”
Section: Confirmedcontrasting
confidence: 76%
“…Others chose to focus on one aspect of the triad at a time, e.g. skill-based (Olutuase, Brijlal, and Yan 2020) or affective (Keller and Kozlinska 2019).…”
Section: Experiential Entrepreneurship Pedagogymentioning
confidence: 99%
See 1 more Smart Citation
“…Liñán [71] found a significant positive association between entrepreneurial skills and intention among university students. Their study also established that a large part of entrepreneurial achievement relies on skills more than it does on the experience or education of young people [72]. Skills have the potential for long-term growth in the field [73].…”
Section: Mediating Role Of Entrepreneurial Skillsmentioning
confidence: 96%
“…The influence of national culture and contexts on student entrepreneurship (cf. Olutuase et al, 2020;Shirokova et al, 2018) was outside the scope of this research. Therefore, we suggest that future researchers conduct multiple case studies to consider contextual differences in their analysis or qualitative comparative analysis (cf.…”
Section: Limitations and Research Outlookmentioning
confidence: 99%